Safety of the plastibell circumcision in neonates, infants and older children - Razzaq, Sajid; Mehmood, Muhammad Sajid; Tahir, Tufail Hussain; Masood, Tariq; Ghaffar, Salma (International Journal of Health Sciences, 2018)
Objectives: The objectives of this study were to determine the safety of the Plastibell device (PD) circumcision in neonates, infants, and older children. Patients and Methods: A prospective, descriptive study was conducted in private clinics of district Poonch and district Sudhanuti Azad Kashmir, Pakistan, during the period from November 2014 to August 2017. Research was conducted in light of guidelines set by Helsinki declaration. Healthy male babies free of any clinical signs of illness and congenital anomaly were included in the study. The babies having weight <3 kg at the time of surgery were excluded from the study. The parents/guardian were explained about the procedure and informed consent was taken. The complications that developed postoperatively were recorded. The record of all cases was analyzed retrospectively for safety outcome and complications developed in neonates, infants, and older children. Results: A total of 1000 cases including 655 (65.5%) neonates, 241 (24.1%) infants, and 104 (10.4%) children between 1 and 5 years of age were selected. The PD circumcision was done in all these cases. Of these, 93.5% neonates, 89.6% infants, and 66.3% children older than 1 years of age had no complications postoperatively. The complication rate was highest among the children between 1 and 5 years of age as compared to neonates and infants. The complications such as bleeding prepuce, hematoma, and swelling prepuce were higher in infants than neonates while superficial infection and buried glans were noted more in neonates than infants. Conclusion: It may be inferred from our findings that Plastibell circumcision is safer if done in the 1st year of life and younger the age better is prognosis in healthy male babies.